2022
DOI: 10.1097/mpg.0000000000003527
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Beliefs in Children and Adolescents with Inflammatory Bowel Disease and their Parents

Abstract: Objectives: Patients with inflammatory bowel disease (IBD) may have diet-related beliefs that lead to restrictive dietary behaviours. This study aimed to evaluate dietary beliefs in young patients with IBD and their parents and the presence of restrictive behaviours. Methods: A questionnaire regarding dietary beliefs was administered to IBD patients aged 8-17 years and their parents. A Food Frequency Questionnaire was administered to patients with IBD and a peer control group. Results: Seventy-five patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…A similar study in pediatric CD patients in clinical remission showed lower fiber and vitamin A intake, along with higher animal protein consumption; also in this study, ORAC was lower, while PRAL was higher in CD patients compared to healthy subjects [106]. These data are consistent with epidemiological studies showing that parents of pediatric IBD patients pay particular attention to highly processed foods, fast foods, spicy foods and dairy products, but little attention to meat consumption, with a tendency to believe that fruits and vegetables may have a negative impact on the disease course [107,108].…”
Section: Food Habits-related Causes Of Malnutritionsupporting
confidence: 89%
“…A similar study in pediatric CD patients in clinical remission showed lower fiber and vitamin A intake, along with higher animal protein consumption; also in this study, ORAC was lower, while PRAL was higher in CD patients compared to healthy subjects [106]. These data are consistent with epidemiological studies showing that parents of pediatric IBD patients pay particular attention to highly processed foods, fast foods, spicy foods and dairy products, but little attention to meat consumption, with a tendency to believe that fruits and vegetables may have a negative impact on the disease course [107,108].…”
Section: Food Habits-related Causes Of Malnutritionsupporting
confidence: 89%
“…However, by relying solely on the BMI, we may underestimate patients who are malnourished due to an inappropriate diet but whose BMI levels are normal or even high. These patients frequently used elimination diets to control disease symptoms and maintain clinical remission [ 58 , 59 ]. Meanwhile, avoiding certain alimentary products and/or groups of alimentary products increases the risk of micronutrient deficiencies, even if the patients’ energy intake is sufficient and they maintain a normal or even increased BMI.…”
Section: Discussionmentioning
confidence: 99%